2015
DOI: 10.1161/hypertensionaha.115.05773
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Intervention of the Effects of Alcohol on Blood Pressure in Premenopausal Women

Abstract: A fter the effects of body weight, alcohol consumption is one of the strongest potentially modifiable risk factors for hypertension.1 Paradoxically, several cross-sectional epidemiological studies suggest that low-level alcohol consumption (4-7 drinks/wk) associates with lower blood pressure (BP) in women, with curvilinearity of the alcohol-BP relationship more marked in women compared with men.2,3 However, associations between alcohol intake and hypertension have not been as extensively evaluated in women and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…We judged 12 studies from 11 trials to be of high technical quality. 911,23,24,26,29,30,32,33,40,41 Only three trials presented data for women, 28,50,53 making pooled effect estimates uncertain. One trial reported office blood pressure in one report, 9 and ambulatory blood pressure monitoring in a much smaller substudy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We judged 12 studies from 11 trials to be of high technical quality. 911,23,24,26,29,30,32,33,40,41 Only three trials presented data for women, 28,50,53 making pooled effect estimates uncertain. One trial reported office blood pressure in one report, 9 and ambulatory blood pressure monitoring in a much smaller substudy.…”
Section: Resultsmentioning
confidence: 99%
“…Because only three trials reported results for women, 28,50,53 we have less confidence in the pooled effect estimates. Similarly, there was only one trial in people with hypertension who consumed three or fewer drinks per day.…”
Section: Discussionmentioning
confidence: 98%
“…1 The causal impact of alcohol consumption on coronary heart disease and conditions related to atherosclerosis has not yet established, despite its public health importance and the numerous studies that have addressed this issue. [2][3][4][5] Although randomized controlled trials on the effects of alcohol consumption on cardiovascular risk factors have been conducted, 4,6,7 it is difficult to implement such trials in a way that produces sustained large differences in alcohol consumption. Studies using genetic information as instrumental variables (IVs), such as Mendelian randomization studies, 8 have presented better evidence regarding the relationship between alcohol consumption and cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between increasing average daily alcohol consumption and the incidence of cirrhosis and pancreatitis and subsequent mortality from these diseases is exponential 19,20 . The rise in cirrhosis mortality has been so striking in the UK over the past 20 years that it is likely that the effects of alcohol and have been shown to negate any protective effect from low-level drinking on coronary heart disease 32 , and an RCT published in 2015 reported that regular low levels of alcohol consumption increases the risk of hypertension among women 33 . In addition, Mendelian randomization studies that more closely replicate RCTs than traditional observational studies have called into question the veracity of the apparent protective effects of alcohol against cardiovascular disease, as well as several key hypothesized causal mechanisms 34,35 .…”
Section: Gastrointestinal and Hepatic Diseasesmentioning
confidence: 99%